Sense & respond - Gothelf, Jeff (Harvard Business Review Press, 2017)
This is no mere tech issue. The transformation requires a complete rethinking of the way we organize and manage work. And, as software becomes ever more integrated into every product and service, making this big shift is quickly becoming the key operational challenge for businesses of all kinds. We need a management model that doesn’t merely account for, but actually embraces, continuous change. Yet the truth is, most organizations continue to rely on outmoded, industrial-era operational models. They structure their teams, manage their people, and evolve their organizational cultures the way they always have